2019
DOI: 10.1161/circresaha.118.313911
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Distinct Immune Phenotypes Using Machine Learning in Pulmonary Arterial Hypertension

Abstract: In December 2018, the average time from submission to first decision for all original research papers submitted to Circulation Research was 14.99 days. ABSTRACTRationale: Accumulating evidence implicates inflammation in pulmonary arterial hypertension (PAH) and therapies targeting immunity are under investigation, though it remains unknown if distinct immune phenotypes exist.Objective: Identify PAH immune phenotypes based on unsupervised analysis of blood proteomic profiles. Methods and Results:In a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 51 publications
4
122
2
2
Order By: Relevance
“…In a recent study, cytokine clusters were made in PAH patients using machine learning. The analyses showed that the immune phenotypes were not dependent upon the subtypes within the WHO Group 1 PAH classification [108], indicating that immune phenotypes may vary within the WHO Group 1 subtypes. Furthermore, these findings might provide a framework to examine patient responses to emerging therapies targeting immunity in the future.…”
Section: Inflammatory Diagnostic and Prognostic Biomarkers In Pah Andmentioning
confidence: 93%
“…In a recent study, cytokine clusters were made in PAH patients using machine learning. The analyses showed that the immune phenotypes were not dependent upon the subtypes within the WHO Group 1 PAH classification [108], indicating that immune phenotypes may vary within the WHO Group 1 subtypes. Furthermore, these findings might provide a framework to examine patient responses to emerging therapies targeting immunity in the future.…”
Section: Inflammatory Diagnostic and Prognostic Biomarkers In Pah Andmentioning
confidence: 93%
“…In murine models, overexpression of IL-6 leads to the development of pulmonary vascular lesions [5], IL-6 deficient mice are protected [6] and administration of an IL-6R neutralising antibody attenuates the development of experimental PAH [7]. Looking wider than IL-6 signalling, there is broad acceptance that inflammation plays an integral part in PAH pathobiology [8,9]. The wealth of preclinical data provided a solid platform from which the clinical tractability of inflammation in patients with PAH was to be explored.…”
mentioning
confidence: 99%
“…This may explain why various immune diseases are remarkably more frequent in women and why many immune diseases, such as systemic sclerosis (SSc), lupus, and mixed connective tissue disease, are associated with increased risk of PAH [117]. Furthermore, recently distinct immune phenotypes have been reported in PAH patients [118]. In experimental PH, dysregulated immunity in the form of deficient regulatory T-cell (Treg) activity contributes to increased inflammation [20].…”
Section: Anti-inflammatory and Immunomodulatory Effects Of 2mementioning
confidence: 99%